2014
DOI: 10.1007/s13346-014-0204-0
|View full text |Cite
|
Sign up to set email alerts
|

Pouch drug delivery systems for dermal and transdermal administration

Abstract: In this work, we have designed and investigated a new carrier for dermal and transdermal drug delivery. The delivery system is composed of high (>60 %) ethanol concentration, phospholipid, polymer, and water. The system forms a structured matrix following non-occluded application on the skin. We call these structured carriers as pouch drug delivery systems (PDDS). The pouch-structured matrix was characterized by electron microscopy, (31)P-NMR and FTIR. The new delivery system exhibits a number of properties ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…In our previous study on Weblike delivery systems, 31 P-NMR spectra suggested a reverse micellar organization of phospholipid in high ethanolic solutions [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous study on Weblike delivery systems, 31 P-NMR spectra suggested a reverse micellar organization of phospholipid in high ethanolic solutions [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…A weblike carrier comprises phospholipid, ethanol, a film-forming polymer and optionally water. Additives such as glycols, Vit E and ethyl acetate can also be part of the Weblike carrier [ 17 , 18 ]. The Weblike carrier that we call Cannaweb contains added HSO to enhance the dermal and transdermal delivery of lipophilic molecules such as cannabinoids [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is a critical concentration of ethanol that may cause a destabilization due to phospholipid bilayers interdigitation [148]. Multiple studies showed the effectiveness of ethosomes for dermal drug delivery in occlusive and nonocclusive applications [141,150,151], and demonstrated their excellent ability to enhance the cutaneous permeation of drugs, including highly lipophilic and highly hydrophilic active compounds [147,[152][153][154].…”
Section: Nanovesicular Carriersmentioning
confidence: 99%